Prime-boost vaccination strategy with bacillus Calmette–Guérin (BCG) and liposomized alpha-crystalline protein 1 reinvigorates BCG potency. (3rd June 2015) - Siddiqui, K F; Amir, M; Khan, N; Rama Krishna, G; Sheikh, J A; Rajagopal, K; Agrewala, J N
Summary: Bacillus Calmette–Guérin (BCG) remains the only available and most widely administered vaccine against Mycobacterium tuberculosis (Mtb), yet it fails to protect vaccinated individuals either from primary infection or reactivation of latent tuberculosis (TB). Despite BCG's variable efficacy against TB, the fact remains that BCG imparts protection in children against the disease, indicating that BCG possesses a wide protective antigenic repertoire. However, its failure to impart protection in adulthood can be linked to its failure to generate long-lived memory response and elicitation of an inadequate immune response against latency-associated antigens. Therefore, to improve the protective efficacy of BCG, a novel vaccination strategy is required. Consequently, in the present study, we have exploited the vaccination potential of liposomized α-crystalline 1 (Acr1L), a latency-associated antigen to induce enduring protective immunity against Mtb in BCG-primed animals. It is noteworthy that an increase in the multi-functional [interferon (IFN)-γ hi /tumour necrosis factor (TNF)-α hi ] CD4 and CD8 T cells were observed in BCG-primed and Acr1L-boosted (BCG-Acr1L) animals, compared to BCG alone. Further, substantial expansion of both central memory (CD44 hi /CD62L hi ) and effector memory (CD44 hi /CD62L lo ) populations of CD4 and CD8 T cells was noted. Importantly, BCG-Acr1L exhibited significantly better protection than BCG, as evidenced by a reduction in the bacterial burden and histopathological data of the lungs. In essence, BCG-Acr1L could be a potent future vaccination strategy to reinvigorate BCG potency.